Report of the Working Group on Hill Areas Development Programme/Western Ghats Development Programme for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The approach and strategy of the programme have evolved through the Plans. The programmes implemented during the Fifth Plan period were mainly beneficiary oriented. During the Sixth Plan, though the emphasis shifted to eco- development, the general tenor of HADP remained substantially the same as that of normal State Plan following the same sectoral approach. The Seventh Plan laid particular emphasis on the development of ecology and environment, namely eco- restoration, eco-preservation and eco-development. The aim was to evolve plans and programmes which would stimulate socio-economic growth, development of infrastructure and promotion of ecology of the areas covered by HADP.
Government of India, Planning Commission
Government of India, Planning Commission